PHOTOCATALYTIC DEGRADATION OF ORGANIC POLLUTANTS USING METAL-OXIDE NANOSTRUCTURES - Ubaid Ullah; Tanzeela Faiz; Mirza Aqeel Ur Rehman; Muhammad Zeeshan; Saira Tariq; Syed Aman Ullah Shah Bukhari; Muhammad Ahmad; Fatima Malik; Abdul Nabi Jakhrani; Muhammad Zeshan Azam (Spectrum of Engineering Sciences, 2025)
The increasing contamination of freshwater resources by persistent organic pollutants necessitates the development of efficient and environmentally friendly treatment technologies. This study investigates the photocatalytic degradation of organic dyes using nanostructured metal oxides synthesized via sol-gel and hydrothermal methods. Titanium dioxide TiO₂, zinc oxide ZnO, and iron oxide Fe₂O₃ nanostructures were fabricated and characterized using SEM, FTIR, XRD, and UV-Vis spectroscopy to determine their structural, morphological, and optical properties. SEM images confirmed well-dispersed nanostructures with varied morphologies, while FTIR and XRD validated the presence of functional groups and crystalline phases essential for photocatalytic activity. UV-Vis analysis demonstrated significant degradation of dyes such as methylene blue, Rhoda mine B, and methyl orange under UV and visible light irradiation. The photocatalytic efficiency was evaluated under various parameters including catalyst dosage, dye concentration, pH, and light source. Kinetic modeling revealed that the degradation followed pseudo-second-order kinetics, indicating surface-mediated chemisorption as the dominant mechanism. Furthermore, reusability experiments confirmed the structural stability and recyclability of the catalysts over multiple cycles. The findings highlight the potential of green-synthesized metal-oxide nanostructures as sustainable catalysts for the effective removal of organic pollutants from wastewater.